2019
DOI: 10.3390/nu11081900
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Omega-3 Polyunsaturated Fatty Acids Reduces Opioid-Seeking Behaviors and Alters the Gut Microbiome

Abstract: Opioids are highly addictive substances with a relapse rate of over 90%. While preclinical models of chronic opioid exposure exist for studying opioid dependence, none recapitulate the relapses observed in human opioid addiction. The mechanisms associated with opioid dependence, the accompanying withdrawal symptoms, and the relapses that are often observed months or years after opioid dependence are poorly understood. Therefore, we developed a novel model of chronic opioid exposure whereby the level of adminis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…Given current research in the area of psychopathology and the gut microbiota, Lactobacillus and Bifidobacterium, though Bifidobacterium was not included among the differentially abundant genera in the present analysis, may warrant further study. Opioid-related alterations in these genera were found to be reversible by omega-3 polyunsaturated fatty acid 19 and probiotic administration 11 , and they exhibited bile-salt hydrolase activity 54 in prior work. Moreover, certain Lactobacillus and Bifidobacterium species may impact anxiety and depressive symptoms 55 57 .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Given current research in the area of psychopathology and the gut microbiota, Lactobacillus and Bifidobacterium, though Bifidobacterium was not included among the differentially abundant genera in the present analysis, may warrant further study. Opioid-related alterations in these genera were found to be reversible by omega-3 polyunsaturated fatty acid 19 and probiotic administration 11 , and they exhibited bile-salt hydrolase activity 54 in prior work. Moreover, certain Lactobacillus and Bifidobacterium species may impact anxiety and depressive symptoms 55 57 .…”
Section: Discussionmentioning
confidence: 90%
“…Our study was unable to perform the metabolomic analysis required to confirm that the lower abundance of Roseburia species observed in participants exposed to opioid agonists related to lower levels of butyrate in the gut environment. However, recent studies using murine models highlight that probiotic administration 11 and potentially butyrate 6 are associated with decreased opioid antinociceptive tolerance and that supplementation with omega-3 polyunsaturated fatty acids attenuates opioid-seeking behaviors and anxiety symptoms during opioid withdrawal 19 . These findings underscore the potential importance of modulating the gut environment to mitigate overdose risk and support OUD recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference may modulate brain function through microbiota-gut-brain axis, and affect symptoms [201]. Increasing evidence has shown that dietary supplementation with omega-3 fatty acids affects gut microbiome [202,203], which in turn, affects neurofunction and mental behaviors [204,205].…”
Section: Possible Mechanisms Underlying the Beneficial Action Of Omegmentioning
confidence: 99%